2012
DOI: 10.1016/j.newast.2011.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic counterparts from counter-rotating relativistic kicked discs

Abstract: We show the results of two dimensional general relativistic inviscid and isothermal hydrodynamical simulations comparing the behavior of co-rotating (with respect to the black hole rotation) and counter-rotating circumbinary quasi-Keplerian discs in the post merger phase of a supermassive binary black hole system. While confirming the spiral shock generation within the disc due to the combined effects of mass loss and recoil velocity of the black hole, we find that the maximum luminosity of counter-rotating di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…In contrast, for a kick oriented perpendicularly to the disk, the resulting concentric density enhancements are weaker and delayed to potentially 1 year after the merger. This general picture of recoil-induced disk perturbations, and the dependence on kick direction, has been substantiated by later studies using full hydrodynamics simulations (Figure 29; Megevand et al, 2009;Rossi et al, 2010;Corrales et al, 2010;Zanotti et al, 2010;Zanotti, 2012;Ponce et al, 2012). Rossi et al (2010), Corrales et al (2010), andZanotti et al (2010) all reach similar conclusions regarding the luminosity and timescale of a recoil-induced afterglow.…”
Section: Afterglows From Gw Recoil Kickssupporting
confidence: 61%
See 1 more Smart Citation
“…In contrast, for a kick oriented perpendicularly to the disk, the resulting concentric density enhancements are weaker and delayed to potentially 1 year after the merger. This general picture of recoil-induced disk perturbations, and the dependence on kick direction, has been substantiated by later studies using full hydrodynamics simulations (Figure 29; Megevand et al, 2009;Rossi et al, 2010;Corrales et al, 2010;Zanotti et al, 2010;Zanotti, 2012;Ponce et al, 2012). Rossi et al (2010), Corrales et al (2010), andZanotti et al (2010) all reach similar conclusions regarding the luminosity and timescale of a recoil-induced afterglow.…”
Section: Afterglows From Gw Recoil Kickssupporting
confidence: 61%
“…Thus, until viscous effects can return the disk to its pre-merger radius, which can take several hundred M of time (amounting to days for a 10 8 M central black hole), the efficiency of emission and hence the luminosity will be less than it was pre-merger. Subsequent studies have confirmed this basic picture (Megevand et al, 2009;Corrales et al, 2010;Anderson et al, 2010;Rosotti et al, 2012;Zanotti, 2012). Whether this effect is detectable depends on variables such as the primary band of emission and the extinction of the center of the host galaxy.…”
Section: Retreat Of the Disk Due To Mass-energy Lossmentioning
confidence: 81%
“…Several authors have discussed the dynamics and related emission from a circumbinary disc with the recoiling central black hole in the post-merger phase (e.g. Lippai et al 2008;Megevand et al 2009;Anderson et al 2010;Corrales et al 2010;Rossi et al 2010;Zanotti et al 2010;Ponce et al 2012;Zanotti 2012;Gold et al 2014b). …”
Section: Motivation For Recoiling Black Hole Researchmentioning
confidence: 99%
“…This is indeed a well-explored area of research, and several studies have investigated the 2D dynamics resulting from a recoiling black hole (e.g. Corrales et al 2010;Zanotti et al 2010;Zanotti 2012) and 3D simulations (e.g. Lippai et al 2008, Megevand et al 2009, Anderson et al 2010, Ponce et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…These effects lead to caustics forming in the perturbed disk, in turn leading to shock heating and potentially both prompt and long-lived EM afterglows [184,165,214,55,268,197,213,269]. Any spin alignment would be critically important for both the character of the prompt EM counterpart, as well as the recoil velocity [159,23].…”
Section: M/hd Simulationsmentioning
confidence: 99%